Bone Marrow Cell Mobilization by the Systemic Use of Granulocyte Colony-Stimulating Factor (GCSF) Improves Wound Bed Preparation. (December 2013) - Iwamoto, Satori; Lin, Xiaofeng; Ramirez, Ron; Carson, Polly; Fiore, David; Goodrich, Jane; Yufit, Tatyana; Falanga, Vincent
Innovative approaches are needed to accelerate the healing of human chronic wounds not responding to conventional therapies. An evolving and promising treatment is the use of stem cells. Our group has previously described the use of expanded (in vitro) autologous stem cells aspirated from human bone marrow and applied topically in a fibrin spray to human acute and chronic wounds. More recently, we have sought ways to mobilize stem cells directly from the bone marrow, without in vitro expansion. In this report, we show that systemic injections of granulocyte colony-stimulating factor (GCSF) can mobilize stem cells from bone marrow into the peripheral blood and then to the wound site. Our objectives were to optimize parameters for this method by using mouse models and proof of principle in a human chronic wound situation. Mice were injected for 5 days with 2 different formulations of GCSF and compared to control saline. To monitor stem cell mobilization, flow cytometric measurements of Sca-1 and c-Kit and colony-forming cell assays were performed. Full-thickness tail wounds in mice were created and monitored for healing, and polyvinyl alcohol sponges were implanted dorsally to assess collagen accumulation. To determine bone marrow stem cell homing to the wound site, chimeric mice transplanted with Green Fluorescent Protein bone marrow cells were scanned by live imaging. Additionally, as proof of principle, we tested the systemic GCSF approach in a patient with a nonhealing venous ulcer. Our findings lay the ground work and indicate that the systemic administration of GCSF is effective in mobilizing bone marrow stem cells into the peripheral blood and to the wound site. These findings are associated with an increased accumulation of collagen and promising results in terms of wound bed preparation and healing.